The Design and Development of a Tajweed Learning Innovation - Hamir Hamzah, Jaafar; Mohamad Hilmi, Mat Said; Nor Yazi, Khamis (Knowledge E, 2022)
e-Tajweed Yadun is a mobile application developed for learning the science of tajweed effortlessly and efficiently. The application can be simply downloaded and accessed anytime, anywhere. It involves a combination of multimedia and creative graphic elements of a ‘Yadun’ model which is an Arabic term for ‘hand’. e-Tajweed Yadun aims to create an interactive self-learning environment for deeper understanding and memorization of specific tajweed laws that could be burdensome when learned via books and conventional drills. The development of e-Tajweed Yadun involved five phases, namely theoretical study and needs analysis, model development, prototype design, prototype development and evaluation. e-Tajweed Yadun is a new alternative technique to learn the science of tajweed, particularly for Muslim students, as a guide while reading the Qur’an.